A Critical Investigation of the Single Window Concept in the Philippines - Poon, KKO (2011)
The global supply chain is increasingly complex with a lot of players involved in the handling of goods. Firms need to have a logistic system that is able to meet the challenges of moving goods across the border. As the concept of globalization enables the reduction of barriers to trade like tariffs, businesses become more competitive. Manufacturers produce goods that are cheaper and of better quality. However, the efficiencies gained in manufacturing can be lost if the firm is burdened by non-tariff trade barriers. This can be influenced by complex trading procedures and lack of standardization in the systems and information at the port. As such, trade facilitation measures are introduced in order to reduce the compliance burden on the traders and create better customs practices for the government. One of the initiatives being used by the government is the application of the Single Window concept. This paper presents the case on the Single Window initiative and its implementation at a national level. The researcher investigated on the current state of the Philippines with regards to its customs practices. It also discussed in detail the steps being taken for the implementation of the Philippine National Single Window.